TINGKAT PENGETAHUAN ATRESIA BILIER PADA BIDAN DI PUSKESMAS KABUPATEN SIDOARJO - Bagus Setyoboedi; Martono Tri Utomo; Rendi Aji Prihaningtyas; Anindya Kusuma Winahyu; Sjamsul Arief (Universitas Mataram, 2022)
Biliary atresia is the most common cause of cholestasis in infants, which begins with prolonged jaundice. Early detection of biliary atresia in primary healthcare facilities plays an important role in the prognosis and success of treatment. Delay in the diagnosis of biliary atresia is still a problem in the world. Clinically, cholestasis is difficult to distinguish from physiological jaundice. Biliary atresia itself is rarely found in primary health facilities because clinically it is difficult to distinguish from physiological jaundice. Delay in the diagnosis of biliary atresia can increases morbidity and mortality. This activity was carried out in the context of community service, to socialize the level of knowledge about early detection of biliary atresia to health providers, namely midwives. This community service activity was carried out in the form of early socialization of biliary atresia to midwives in Sidoarjo district, East Java. In this study, an initial evaluation of biliary atresia was carried out, then followed by socialization related to biliary atresia and an evaluation after the socialization. A total of 165 midwives participated in this activity with an average age of 40.39 ± 10.09 years. In the initial evaluation of the causes of prolonged jaundice, most of the respondents stated that breastfeeding jaundice and breast milk jaundice were the main causes. As many as 94 (57%) of respondents stated that biliary atresia could be the cause of prolonged jaundice. There was an increase in the level of knowledge about biliary atresia, indicated by the pre-test value of 14.32 ± 2.48 and an increase in the post-test value of 16.51 ± 1.77 and the median value which increased in the pre-test value of 14 to 17 after socialization regarding biliary atresia (p<0.05). This activity supports the need for socialization about early detection of biliary atresia to be carried out massively to health providers in primary health facilities.